The essential Nostradamus : literal translation, historical commentary, and biography - Smoley, Richard, 1956- (J.P. Tarcher/Penguin, 2006)
"A uniquely serious and accessible introduction to the life and work of the mysterious sixteenth-century seer Michel de Nostradamus A uniquely serious and accessible introduction to the life and work of the mysterious sixteenth-century seer Michel de Nostradamus. From his predictions about life and death in the Middle French court of Catherine de' Medici to his uncannily suggestive preconceptions of World War II, Michel de Nostradamus has aroused continual fascination-and commercialization-in the West. Today, many search his elliptical "centuries"--Or collected verses-for new truths about 9/11 and End Times, while supermarket tabloids routinely falsify and exploit his pronouncements. What is the difference between prophecy and prediction, and how has it led to a misuse of the ideas of Nostradamus, as well as those of other post-biblical prognosticators? What is the nature of the oracular tradition in the West-stretching back to the oracle at Delphi-and how can Nostradamus be understood from this perspective? In The Essential Nostradamus, the highly regarded spiritual thinker and writer Richard Smoley provides a true sourcebook in the life and messages of one of history's most peculiar figures. This volume offers a host of advantages beyond other collections of Nostradamus's work. Many commentators on Nostradamus take liberties in their translations, further confusing the matter of what the prophetic quatrains actually said. In The Essential Nostradamus, Smoley presents a fresh, scholarly, and literal translation of Nostradamus's Middle French, allowing readers to make their own determination as to the passages' historical references and accuracy. Smoley also supplies detailed commentary on Nostradamus's key quatrains, with a sharp eye toward the political and social events of the writer's era-elements that many commentators overlook or fail to grasp. An authoritative biographical essay-highlighting Nostradamus's separate roles as physician, astrologer, and prognosticator-rounds out the volume to create a truly essential exposition of the work of one of Western culture's most mysterious men."--Publisher's website.